Design and development of multi-band multi-generation compatible MIMO antenna for wireless devices - Biswas, Arumita; Gupta, Vibha Rani (Engineering and Applied Science Research, 2020)
A planar dual-element multi-generation compatible MIMO antenna is presented in this paper. The radiating antenna elements are designed to resonate over two frequency ranges: 1.41 GHz – 2.11 GHz and 3.6 GHz – 3.8 GHz, with (S11/S22) reference considered as -10 dB,covering frequencies allotted for L1 GPS, 2G standards (GSM-1800 and GSM-1900), 3G standard (UMTS), LTE (working on TDD and FDD techniques) and 5G New Radio. The designed antenna is optimized using IE3D simulation software and fabricated on FR4 substrate having relative permittivity of 4.4, loss tangent of 0.02 and thickness of 1.6 mm. A three step isolation improvement and impedance bandwidth enhancement technique is presented to reduce the mutual coupling and cover the desired frequency range. Antenna characteristics in terms of the reflection coefficient, mutual coupling, radiation pattern and gain are measured and show good agreement with the simulated results. Diversity performance is evaluated in terms of the envelop correlation coefficient. It is found to be less than 0.12 and 0.06 in the first and second bands of frequencies, respectively. The planar structure and capability to support several frequencies of multiple generations make the proposed MIMO antenna a good candidate for integration with future wireless devices.